SOCIALIZATION OF THE USE OF PARENTAL CONTROL APPLICATION IN USING THE INTERNET ON ONLINE LEARNING PROCESSES DURING COVID-19 PANDEMIC - Syarifah Farissi Hamama; Maulida Maulida; Samsuar Samsuar; Syarifah Fadiya Hallaby; Hasanah Hasanah (Universitas Muhammadiyah Aceh, 2022)
The Covid-19 pandemic condition requires the world of education to change the learning system from a face-to-face to an online learning process. The internet is one of the media that can help teachers and students in the teaching and learning process. The use of internet media for learning during the pandemic must still be in the guidance of teachers and parents. Internet media is a media without limit, a variety of information that is often unfiltered is available in the virtual world. So clear and firm guidelines are needed regarding the use of the internet for students. This service activity was held on 14-15 January 2022, at Gampong Peurada 1 Banda Aceh. The choice of location for the activity is because Gampong Peurada is one of the Red Zone areas for the Covid-19 Pandemic in 2021. The results of the socialization show that generally parents are still not aware of the use of Parental Control applications in the online learning process.Keywords: Covid-19, internet usage, learning process, parental control.